Edukasi Adaptasi Kebiasaan Baru Pada Masa Pandemi Covid-19 - Sri Mulyaningsih; Lida Amalia; Hudiana Hernawan; De Budi Irwan Taofik; Dewi Hernawati (Jurnal Pekemas, 2020)
Indonesia and other countries in the world are currently facing a deadly disease outbreak, namely Covid-19. This outbreak is known as the Covid-19 pandemic. The number of victims who died in Indonesia has more than 250 thousand people. Until now, there is still no medicine or vaccine that can cure this disease. Therefore, the number of victims who die every day is still happening. This causes the corona virus that causes Covid-19 to still not disappear from people's lives. The way out to break the chain of transmission of corona virus infection is the 'new normal' adaptation. New Normal "is narrated as" New Habit Adaptation ". The purpose of the New Habit Adaptation is so that we can work, study and have productive activities in the era of the Covid-19 pandemic. New habits for healthier living must be continuously carried out in society and in every individual, so that they become social norms and new individual norms in everyday life. The adaptation of this new habit must continue to be socialized in the lives of all of us, one of which is in the education community, namely at SMPN1 Banyuresmi Garut